Project Based Learning with Socio Scientific Issues in Improving Junior High School Students' Habits of Mind on Biotechnology Material (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2025)
The development of science and technology requires students to have Habits of Mind (HoM) to be able to think critically, creatively, and reflectively in dealing with complex problems. This study aims to determine the effect of the Socio-Scientific Issues-based Project-Based Learning (PJBL-SSI) model on changes in students' HoM on biotechnology material. Socio-Scientific Issues context, such as gluten-free diet trend, was chosen to encourage real problem-based learning and project-based decision making. The study employed a quasi-experimental method with a Non-equivalent Control Group Design, involving 62 ninth-grade students from Bandung City Public Junior High School. The experimental group received PJBL-SSI learning, while the control group used conventional PJBL. Data were collected through validated HoM pretest and posttest questionnaires. The results showed an increase in the mean score of HoM in the experimental group from 38.23 to 44.97, while the control group decreased from 41.62 to 40.90. The Mann-Whitney U test showed a significant difference between groups (p = 0.006). These findings support previous studies that the integration of PPA and SSI is effective in shaping students' reflective and critical thinking dispositions through contextual projects and meaningful ethical discussions.